Stephen Biesty's castles - Hooper, Meredith (Enchanted Lion Books, 2004)
"This is a book about ten real castles. Each castle is illustrated by a fabulous cross-section that reveals its interior, and is described by a lively text on an important day in its history"--Front jkt. flap.